The evolution of the sales and operations planning - Padilla-Solís, Julio Alejandro (2014)
The sales and operations planning process has to continually evolve before the new integration dimensions in the company supply and demand areas; for many years this concept has not been well understood in the companies. The inputs and outputs of this process should be clearly individualized and accepted as responsibilities of a determined business area. A new management architecture, corresponding to this scenario, is proposed and discussed in this document. A review of the computer support requirements for this process is undertaken. The required logic is also explained, highlighting the problems of corporate culture that arise in response to these changes and how they should be avoided. The common mistakes that companies make facing this need and the key success factors for an adequate deployment are also pointed out.